P- SOLUBILIZING MICROORGANISMS PERFORMANCE ON MANURE AND ROCK PHOSPHATE AND THEIR INFLUENCES ON SOIL AND PLANT PHOSPHOROUS IN CALCAREOUS SOILS - Umar, M. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Phosphate solubilizing microorganisms were isolated in vitro experiment, and wheat crops were planted in pots for 5 months and treated with rock phosphate, manure and with combination treatments of rock phosphate, manure, and phosphate solubilizing microorganisms to compare with control treatment. The result shows that the solubilizing index ranged between 1.4 to 1.6 for isolated microorganisms, the decrease in soil pH which has an enormous influence on phosphate solubility were significantly influenced by the addition of phosphate solubilizing microorganisms, and manure is 6.5 pH comparing with 8 pH for control. Soil soluble and extractable phosphorous also increased by a combination of phosphate solubilizing microorganisms and manure recording 0.46±0.03 ppm and 10.7±1.01 ppm respectively comparing to 0.39±0.01 ppm and 0.75±0.11ppm for control after one month of the experiment, and this significance continued to 3 and 5 months after planting followed by the combination treatment of rock phosphate and phosphate solubilizing microorganisms. Total phosphorous in both wheat shoot and root after 5 months of planting were increased significantly by the addition of phosphate solubilizing microorganisms and manure to record 0.792±0.11% in shoot and 0.66±0.13% in roots and more than other treatments, however the translocation of phosphorous is harder than nitrogen from roots to shoots. The addition of phosphate solubilizing microorganisms enhanced the growth ratio of wheat up to 96±5 comparing to 40±3 for control.